Space defence legal regime in the service of sustainable development - Malinowska, Katarzyna (European Integration Studies, 2024)
This article examines the challenges and opportunities of military space activities in the context of the sustainable development of space exploration. It investigates the legal frameworks governing military use, focusing on the need for regulations to address risks such as space debris caused by anti-satellite testing, as well as space governance issues. It analyses the role of international, regional (EU), and national laws and policies in achieving a sustainable and responsible exploration of outer space. The role of international and regional bodies such as the UN and EU in achieving sustainability goals is analysed in terms of the synergy between civil and military uses of space.